Speaking of Dance Twelve Contemporary Choreographers on Their Craft. Book review - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2005)
PALABRAS CLAVE: Contemporary Choreographers, Merce Cunningham, Paul Taylor, Twyla Tharp, Trisha Brown, Lucinda Childs, David Gordon, Meredith Monk, Bill T. Jones, Mark Morris, Eiko Otake, Takashi Koma Otake, John R. Jasperse, Ann Carlson.
Speaking of Dance: Twelve Contemporary Choreographers on Their Craft. Joyce Morgenroth, Routledge, 2004.